2014
DOI: 10.1021/jo501383v
|View full text |Cite
|
Sign up to set email alerts
|

Diisobutylaluminum Hydride Promoted Cyclization of o-(Trimethylsilylethynyl)styrenes to Indenes

Abstract: The reaction of o-(trimethylsilylethynyl)styrenes with diisobutylaluminum hydride (DIBAL-H) provides 2-trimethylsilyl-1H-indenes efficiently. The cyclization mechanism involves regioselective hydroalumination of the alkynyl moiety, geometrical isomerization of the alkenylaluminums formed, and intramolecular carboalumination. With substrates bearing a 2-(trimethylsilyl)ethenyl group (R(1) = Me3Si, R(2) = R(3) = H), bis-silylated benzofulvenes are obtained upon treatment of the reaction mixture with an excess am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The bond distances in the six-membered azaborine ring are consistent with previously reported bond lengths for monocyclic azaborines with the exception of the bridging B–C bond (bond distance highlighted in red), which is significantly longer than that found in typical monocyclic azaborine structures (1.568(3) Å vs ∼1.52 Å) . An elongation of the bridging C–C bond in the indene/indenyl system is also observed upon deprotonation, but to a somewhat lesser extent (∼1.437 Å for Li indenyl vs ∼1.40–1.41 Å for indene). The bridging B–C distance of 1.568 Å approaches that of a B­(sp 2 )–C­(sp 2 ) single bond (e.g., 1.574 Å observed for a B -Ph-substituted 1,2-azaborine).…”
supporting
confidence: 89%
“…The bond distances in the six-membered azaborine ring are consistent with previously reported bond lengths for monocyclic azaborines with the exception of the bridging B–C bond (bond distance highlighted in red), which is significantly longer than that found in typical monocyclic azaborine structures (1.568(3) Å vs ∼1.52 Å) . An elongation of the bridging C–C bond in the indene/indenyl system is also observed upon deprotonation, but to a somewhat lesser extent (∼1.437 Å for Li indenyl vs ∼1.40–1.41 Å for indene). The bridging B–C distance of 1.568 Å approaches that of a B­(sp 2 )–C­(sp 2 ) single bond (e.g., 1.574 Å observed for a B -Ph-substituted 1,2-azaborine).…”
supporting
confidence: 89%
“…Tris(macrocycle)s 3 are 1,3,5-/2,4,6-differentiated hexakis(phenylethynyl)benzenes (HPEBs) 10 and we started with 1,3,5-trichloro-2,4,6-tris(2-trimethylsilylethynyl)benzene 6 . 11 Stepwise Sonogashira coupling reactions of aryl iodides ( 10 12 and 11 5 ) with desilylated acetylenes on 6 and on the resulting 7 gave trichloro-intermediates 8 . The third Sonogashira coupling of aryl acetylenes ( 12 5 ) with the chlorides 13 on 8 furnished HPEB 9 , a threefold ring-closing precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic experiments showed that the intramolecular carboalumination reaction proceeded through a syn -addition. 82 83 At higher temperature, the related enyne 128 underwent skeletal rearrangement to form 1,2-dihydronaphthalen-1-ylaluminum reagent 131 via a cyclopropylcarbinylaluminum species 130 (Scheme 31b ). 84 Subsequent dehydroalumination formed the naphthalene 132 .…”
Section: Uncatalyzed Carboalumination Of Alkenesmentioning
confidence: 99%